If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 + d = -53 Solving -23 + d = -53 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + d = -53 + 23 Combine like terms: -23 + 23 = 0 0 + d = -53 + 23 d = -53 + 23 Combine like terms: -53 + 23 = -30 d = -30 Simplifying d = -30
| 4x^2=24+4y | | 2x^2-20n=-48 | | 37x-20= | | 14z-3z= | | .33(p+1)=.5(p-2) | | 5x+376=-50 | | (4n+1)(2n-3)=0 | | -3.5-x=7.2 | | (x^3/4)=16 | | x^3/4=16 | | M/-7=-28 | | 45+6x=29 | | (3x-6)(4x+6)= | | 2x^2+11xy-121y^2= | | (9+2x)3=4x+11 | | If(x+5)=x^2+kx+30 | | 12cos^2(x)+8cos(x)-20=0 | | 56x+20y=1900 | | 8-7p=10p | | (6b+1)(2b-4)= | | 2x^2+2y^2+4xy-4=0 | | (9c/10b)/(3c/2b^3c4)= | | 9c/10b= | | 30=67t-5t^2 | | 0.53KG=XG | | 2ln(r)=ln(15r+34) | | 0=130-6t-16t^2 | | 2(3X-2)=4x-14 | | 21=5+34t-16t^2 | | -3+.5y=4x+11 | | f(0)=4x-16 | | 2(u-4)-7u=-13 |